Seven new mitochondrial genomes of phytophagous scarab beetles (Coleoptera: Scarabaeidae) and phylogenetic implications - Li, Yujie; Nie, Rui-E; Lu, Yuanyuan; Lee, Seunghyun; Zhao, Zhengyu; Wu, Ling; Sun, Hongying; Bai, Ming (Zootaxa, 2022)
Among Scarabaeidae, the phytophagous scarab lineage including Melolonthinae, Cetoniinae, Dynastinae, and Rutelinae is considered important due to its members’ roles as agricultural pests or pollinators. In this study, the near-complete mitochondrial genomes of seven species from six genera in the phytophagous scarab lineage were newly sequenced: Anomala russiventris (Fairmaire, 1893); Apogonia cf. basalis (Moser, 1915); Apogonia splendida (Boheman, 1858); Coenochilus striatus (Westwood, 1874); Trichogomphus mongol (Arrow, 1908); Sophrops subrugatus (Moser, 1921) and Tetraserica leishanica (Liu, Bai, Yang & Ahrens, 2014). The complete mitochondrial genomes from the 6 species include 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), 2 ribosomal RNA genes (rRNAs), and 1 control region, which have a highly conserved gene arrangement, except for Tr. mongol with the rearrangement of 2 tRNA genes (tRNA-Ile and tRNA-Gln), which is a potential identified subfamily-level character of Dynastinae. In order to test whether the mitogenomic data are suited for high-level phylogenetic inferences, the substitution saturation and heterogeneity were analyzed. The results showed no sign that the phylogenetic inferences were biased by substitution saturation or the low heterogeneity of the sequence composition for most pairwise comparisons between the sequences for the entire dataset (13 PCGs) and the amino acids dataset (13 PCGs_AA). Based on the combined data of 13 PCGs and 13 PCGs_AA from the mitogenomes of 37 taxa, the phylogeny of the phytophagous lineage was explored using RAxML and Bayesian methods. The results confirmed that Cetoniinae, Rutelinae, and Dynastinae are monophyletic, and that the latter two are sister groups. Melolonthinae is a paraphyletic group, and its tribes, Diplotaxini, Euchirini, Melolonthini, Rhizotrogini, and Sericini, are a monophyletic group. The subfamily rank of Dynastinae and the tribe rank of Anomalini and Adoretini are supported.